2010
DOI: 10.1128/jcm.00309-10
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Acanthamoeba Cysts to Disinfection Treatments Used in Health Care Settings

Abstract: Free-living amoebae that belong to the genus Acanthamoeba are widespread in the environment, including water. They are responsible for human infections and can host pathogenic microorganisms. Under unfavorable conditions, they form cysts with high levels of resistance to disinfection methods, thus potentially representing a threat to public health. In the present study we evaluated the efficacies of various biocides against trophozoites and cysts of several Acanthamoeba strains. We demonstrated that disinfecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
115
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(123 citation statements)
references
References 61 publications
7
115
1
Order By: Relevance
“…Sodium hypochlorite, or household bleach, is known to have a broad spectrum of antimicrobial activity and is already widely used in the food industry, e.g., for sanitizing food contact surfaces. The effectiveness of hypochlorite in killing Acanthamoeba cysts (17,21,22) has been confirmed in the present study. The microbiocidal activity of chlorine is mainly attributed to undissociated hypochlorous acid, but the exact action mechanisms are still unknown.…”
Section: Discussionsupporting
confidence: 73%
“…Sodium hypochlorite, or household bleach, is known to have a broad spectrum of antimicrobial activity and is already widely used in the food industry, e.g., for sanitizing food contact surfaces. The effectiveness of hypochlorite in killing Acanthamoeba cysts (17,21,22) has been confirmed in the present study. The microbiocidal activity of chlorine is mainly attributed to undissociated hypochlorous acid, but the exact action mechanisms are still unknown.…”
Section: Discussionsupporting
confidence: 73%
“…Free-living protozoa on dishcloths are frequently exposed to stress conditions such as desiccation, disinfection and cleaning treatments. Through cyst formation, various protozoan species can survive unfavorable conditions (Aksozek et al, 2002;Coulon et al, 2010;Dupuy et al, 2014;Sriram et al, 2008) which may also be the case on dishcloths.…”
Section: Discussionmentioning
confidence: 99%
“…Encystment has been demonstrated to correlate with development of biocide resistance, with increasing content in alkali-insoluble residues (cellulose) being associated with increasing resistance to most chemical agents (63). Recent studies demonstrated considerable variations in resistance to biocides of closely related Acanthamoeba isolates, suggesting that important variations exist between cyst wall compositions of these isolates (13).…”
Section: Cyst Wall Morphology Of Flamentioning
confidence: 99%